Gastrointestinal Colonization by Candida albicans Mutant Strains in Antibiotic-Treated Mice - Wiesner, Stephen M. (American Society for Microbiology, 2001)
Antibiotic-treated mice orally inoculated with one of three Candida albicans strains (including two mutant strains) or indigenous Candida pelliculosa showed levels of candidal gastrointestinal colonization that were strain specific. However, regardless of strain, the numbers of viable candida were intermediate to high in the stomach, were consistently lowest in the upper small intestine, and increased progressively down the intestinal tract.